Standardisierte Laktatproduktionsrate und Laktateliminationsrate nach maximaler Belastung als Kriterium der Leistungsdiagnostik - Koch, H.; Raschka, C. (Österreichisches Journal für Sportmedizin, 2001)
The separation of production and elimination process of the lactate concentration versus time curve can give additional information in acute exercise tests.